Empty Pericarp24 and Empty Pericarp25 Are Required for the Splicing of Mitochondrial Introns, Complex I Assembly, and Seed Development in Maize - Xiu, Zhihui; Peng, Ling; Wang, Yong; Yang, Huanhuan; Sun, Feng; Wang, Xiaomin; Cao, Shi-Kai; Jiang, Ruicheng; Wang, Le; Chen, Bao-Yin; Tan, Bao-Cai (Frontiers in Plant Science, 2020)
RNA splicing is an essential post-transcriptional regulation in plant mitochondria and chloroplasts. As the mechanism of RNA splicing remains obscure, identification and functional elucidation of new splicing factors are necessary. Through a characterization of two maize mutants, we cloned Empty pericarp 24 (Emp24) and Empty pericarp 25 (Emp25). Both Emp24 and Emp25 encode mitochondrion-targeted P-type PPR proteins. EMP24 is required for the splicing of nad4 intron 1 and 3, which was reported (Ren et al., 2019b), and EMP25 functions in the splicing of nad5 intron 1, 2 and 3. Absence of either Nad4 or Nad5 proteins blocks the assembly of mitochondrial complex I, resulting in the formation of a sub-sized complex I of similar size in both mutants. Mass-spectrometry identification revealed that the subcomplexes in both mutants lack an identical set of proteins of complex I. These results indicate that EMP24 and EMP25 functions in the splicing of nad4 and nad5 introns respectively, and are essential to maize kernel development. The identification of the subcomplexes provides genetic and molecular insights in the modular complex I assembly pathway in maize.